CONCEPT OF TAHKIM IN INDONESIA FOR ISLAMIC BUSI-NESS DISPUTE SETTLEMENT - Daryanto, Daryanto (Journal of Islamic Law Studies, 2021)
In pre-Islamic Arabian, the Concept of Tahkim (arbitration) was known practiced to settle various types of civil commercial disputes. In Islamic law, the concept of Tahkim has not yet become the rule of Islamic law. But concept of Tahkim is still the ideology that can be developed into a basic validity of Arbitration. In the past period, the practice of, Tahkim was often done by the prophet’s friends. The concept of Tahkim in Indonesia is applied for Islamic business dispute settlement, for example Islamic Banking. Indonesia applies the concept of Tahkim which is called “Basyarnas” (Arbitration Institutions). Basyarnas is an institution that resolving disputes based on Islamic principles and run the settlement of disputes in Islamic business sector.